Corporate taxation and the choice of patent location within multinational firms - Tom Karkinsky; Nadine Riedel (Center for Economic Studies and ifo Institute (CESifo), 2009)
Corporate patents are perceived to be the key profit-drivers in many multinational enterprises (MNEs). Moreover, as the transfer pricing process for royalty payments is often highly intransparent, they also constitute a major source of profit shifting opportunities between multinational entities. For both reasons, MNEs have an incentive to locate their patents at affiliates with a relatively small corporate tax rate. Our paper empirically tests for this relationship by exploiting a unique dataset which links information on patent applications to micro panel data for European MNEs. Our results suggest that the corporate tax rate (differential to other group members) indeed exerts a negative effect on the number of patents filed by a subsidiary. The effect is quantitatively large and robust against controlling for affiliate size. The findings prevail if we additionally account for royalty withholding taxes. Moreover, binding `Controlled Foreign Company' rules tend to decrease the number of patent applications.
Keywords: H25; F23; H26; C33; 330; corporate taxation; multinational enterprise; profit shifting